2019
DOI: 10.1177/0163443719876536
|View full text |Cite
|
Sign up to set email alerts
|

Mediatization of a card game: Magic: The Gathering, esports, and streaming

Abstract: Magic: The Gathering is a household name among analog games. Its publisher, Wizards of the Coast, has experimented with digital adaptations since the late 1990s, however, it was only in 2018–2019 when the company announced a more radical push for the video game market, including a strategy for streaming and esports. By analyzing streaming content, paratextual elements, and online discussions leading up to the first major digital tournament, I explore the attempted and heavily promoted transition of Magic: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…As previous scholarship has shown (e.g. Ekström et al, 2016;Švelch, 2020), mediatization is not a linear process. In practice, social and cultural phenomena can co-exist in their unmediated and mediated ways, creating complex feedback loops with zones of resistance on the one hand and pioneer communities on the other (Hepp, 2016;Petersen, 2022).…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…As previous scholarship has shown (e.g. Ekström et al, 2016;Švelch, 2020), mediatization is not a linear process. In practice, social and cultural phenomena can co-exist in their unmediated and mediated ways, creating complex feedback loops with zones of resistance on the one hand and pioneer communities on the other (Hepp, 2016;Petersen, 2022).…”
mentioning
confidence: 85%
“…While analog and video game industries historically operated as two separate ecosystems, Critical Role seems to be situated at their intersection, bringing together tabletop role-playing, video game voice acting, and the platform ecosystem of video game live-streaming (see Taylor, 2018). It is important to note that there have recently been signs of more systemic convergence partly due to successful digital adaptations of analog games (see Švelch, 2020; Trammell, 2019). Aside from gaming-related sponsors, more generalist businesses have also advertised on Critical Role , including NordVPN, the cloud backup service Backblaze, or the online learning platform Skillshare.…”
Section: Methodology and Research Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the historical context and development of loot boxes, it has been suggested that using loot boxes to monetise video games was inspired by how collectible sports cards and fantasy trading cards (e.g., Magic: The Gathering) are sold in blind, randomised packs in order to encourage players to buy more packs and increase revenue [2,4,12]. These randomised packs were designed to contain rare cards, known as 'chase cards,' that were less likely to be included in packs than other cards, and were therefore more sought-after and monetarily valuable.…”
Section: Paid Loot Boxes In Contextmentioning
confidence: 99%